Expression level of serum miR‐374a‐5p in patients with acute pancreatitis and its effect on viability, apoptosis, and inflammatory factors of pancreatic acinar cells induced by cerulein - Fu‐Jun Wang; Xue Mei (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Acute pancreatitis (AP) is one of the life‐threatening diseases of the digestive system. MicroRNA has been asserted to be a regulator of AP. This paper explored the miR‐374a‐5p expression in AP patients and investigated the efficacy of AR42J cells. In this study, 60 healthy people, 58 MAP patients and 58 SAP patients were included, and the serum miR‐374a‐5p levels of the subjects were detected by RT‐qPCR technology. The pancreatitis cell model was structured by stimulating AR42J cells with cerulein. Next, cell viability and apoptosis were detected by CCK‐8 assay and flow cytometry. ELISA was used to measure the concentration of cytokines, such as TNF‐α, IL‐6, and IL‐1β. The data showed that miR‐374a‐5p was downregulated in samples from AP patients, while showing discriminative power for AP populations. Attenuated miR‐374a‐5p were negatively bound up with patients' Ranson score and APACHE II score. Besides, miR‐374a‐5p was declined in cerulein‐treated AR42J cells and forced elevation of miR‐374a‐5p was beneficial to increase cell viability, and inhibit cell apoptosis and inflammation. The present study found that miR‐374a‐5p was reduced in AP serum samples, and up‐regulated expression level of miR‐374a‐5p in cell models had a protective effect on cerulein‐induced inhibition of cell function and inflammatory response.